In Silico Target Identification for Antioxidant and Anti-inflammatory Activity of Oil Palm Leaves Extract after Biotransformation Process - Permatasari, Galuh; Kresnawaty, Irma; Aksa, Annisa Aulia; Santoso, Djoko; Widodo, Widodo (Makara Journal of Science, 2025)
Oil palm leaf extract (OPLE) contains abundant phenolic and flavonoid compounds with recognized antioxidant and anti-inflammatory potential; however, its pharmacological applications remain underexplored. This study aimed to optimize the enrichment process of OPLE and characterize its bioactive compounds using integrated in vitro and in silico approaches. The extraction was optimized by incorporating trichloroacetic acid and extending the incubation time to 48 h, resulting in significantly increased total phenolic content and antioxidant activity compared with the control. LC–MS/MS profiling identified 14 flavonoid compounds with diverse biological functions. Among these, Rhamnetin-3-O-β-D-glucopyranoside, Kaempferol-3-O-rutinoside, and Nelumboroside A exhibited the strongest antioxidant and free radical scavenging activities, while Baicalein-7-O-β-D-glucopyranoside and Kaempferol-3-O-rutinoside demonstrated relatively higher anti-inflammatory potential. Molecular docking and dynamics simulations showed Luteolin as the most promising multifunctional compound, exhibiting stable binding affinities toward LOX5 (−7.5 kcal/mol) and COX2 (−9.6 kcal/mol) targets, with comparable binding residues to the control ligand, Celecoxib. Root mean square deviation and root mean square fluctuation analyses confirmed the stability of the COX2–Luteolin complex, indicating reliable protein–ligand interaction. Furthermore, ADME predictions supported Luteolin’s favorable pharmacokinetic profile, including optimal lipophilicity (logP 0.19) and acceptable oral absorption. Collectively, these results demonstrate the successful optimization of OPLE enrichment and provide molecular-level evidence of its bioactivity. Luteolin emerged as a potential lead compound with balanced antioxidant and anti-inflammatory activities. This study highlights the high biopharmaceutical value of oil palm leaves as a sustainable source of natural therapeutics, promoting their use beyond agricultural waste.